Drug delivery in pluronic micelles: effect of high-frequency ultrasound on drug release from micelles and intracellular uptake - Marin, Alexander (2002)
The effect of high-frequency ultrasound on doxorubicin (DOX) release from Pluronic micelles and intracellular DOX uptake was studied for promyelocytic leukemia HL-60 cells, ovarian carcinoma drug-sensitive and multidrug-resistant (MDR) cells (A2780 and A2780/ADR, respectively), and breast cancer MCF-7 cells. Cavitation events initiated by high-frequency ultrasound were recorded by radical trapping. The onset of transient cavitation and DOX release from micelles were observed at much higher power densities than at low-frequency ultrasound (20–100 kHz). Even a short (15–30 s) exposure to high-frequency ultrasound significantly enhanced the intracellular DOX uptake from PBS, RPMI 1640, and Pluronic micelles. The mechanisms of the observed effects are discussed.